ISLAMIC WEALTH MANAGEMENT: A REVIEW ON THE DIMENSION OF VALUES - Kamri, Nor ’Azzah; Daud, Mohd Zaidi (Jurnal Syariah, 2019)
Wealth is needed for human survival. By nature, people always seek wealth. In Islam, wealth is owned by God and given to man to be dealt with properly. Man only acts as a trustee and manager who is responsible for managing the wealth. Therefore, it is the duty of every Muslim to plan and manage the wealth as prudently as possible based on Islamic law. However, greed and human preoccupation of wealth sometimes lead to the overruling of the halal and haram principle. Unmanaged wealth leads to waste, fraud or freezing of the wealth itself. This is extremely detrimental to wealth owners and the Muslims at large. Based on this, the paper attempts to discuss wealth management in Islam by focusing on the aspect of values. It is important to ensure that the wealth comes from halal (legitimate) sources, spent in the way of Allah, systematically planned, productively developed and ethically managed to be a provision in the future and the hereafter. Therefore, values, such as gratitude, accountability, wise, fair, diligent, productive and futuristic need to be appreciated by every Muslim. These values will guide the planning, spending and managing of wealth wisely, in order to ensure one’s well-being in the world and the hereafter.